Accuracy of Biomarkers for the Diagnosis of Adult Community‐acquired Pneumonia: A Meta‐analysis. (26th February 2020) - Ebell, Mark H.; Bentivegna, Michelle; Cai, Xinyan; Hulme, Cassie; Kearney, Maggie
Abstract: Background: Biomarkers such as C‐reactive protein (CRP) and procalcitonin may help distinguish community‐acquired pneumonia (CAP) from other causes of lower respiratory tract infection. Methods: We performed a systematic review of the literature to identify prospective studies evaluating the accuracy of a biomarker in patients with acute cough or suspected CAP. We performed parallel abstraction of data regarding study inclusion, characteristics, quality, and test accuracy. Study quality was evaluated using QUADAS‐2. Bivariate meta‐analysis was performed using the mada package in R, and summary receiver operating characteristic (ROC) curves were created. Results: Fourteen studies met our inclusion and exclusion criteria; three were at low risk of bias and four at moderate risk of bias, largely due to failure to prespecify diagnostic thresholds. Considering all studies regardless of the cutoff used, CRP was most accurate (area under the ROC curve = 0.802), followed by leukocytosis (0.777) and procalcitonin (0.771). Lipopolysaccharide‐binding protein and fibrinogen are promising, but were only studied in a single report. For CRP and procalcitonin, the positive and negative likelihood ratios (LR+ and LR–, respectively) varied inversely based on the cutoff. For CRP, LR+ and LR− were 2.08 and 0.32 for a cutoff of 20 mg/L, 3.64 and 0.36 for a cutoff of 50 mg/L, and 5.89 and 0.47 for a cutoff of 100 mg/L. For procalcitonin, LR+ and LR− were 2.50 and 0.39 for a cutoff of 0.10 µg/L, 5.43 and 0.62 for a cutoff of 0.25 µg/L, and 8.25 and 0.76 for a cutoff of 0.50 µg/L. The combination of CRP >49.5 mg/L and procalcitonin >0.1 µg/L had LR+ of 2.24 and LR− of 0.44. Conclusions: The best evidence supports CRP as the preferred biomarker for diagnosis of outpatient CAP given its accuracy, low cost, and point‐of‐care availability.